Inhaled diesel exhaust alters the allergen-induced bronchial secretome in humans. Issue 1 (25th January 2018) - Mookherjee, Neeloffer; Piyadasa, Hadeesha; Ryu, Min Hyung; Rider, Christopher Francis; Ezzati, Peyman; Spicer, Victor; Carlsten, Christopher
Diesel exhaust (DE) is a paradigm for traffic-related air pollution. Human adaptation to DE is poorly understood and currently based on oversimplified models. DE promotes allergic responses, but protein expression changes mediated by this interaction have not been systematically investigated. The aim of this study was to define the effect of inhaled DE on allergen-induced proteins in the lung. We performed a randomised and blinded controlled human crossover exposure study. Participants inhaled filtered air or DE; thereafter, contralateral lung segments were challenged with allergen or saline. Using label-free quantitative proteomics, we comprehensively defined DE-mediated alteration of allergen-driven secreted proteins (secretome) in bronchoalveolar lavage. We further examined expression of proteins selected from the secretome data in independent validation experiments using Western blots, ELISA and immunohistochemistry. We identified protein changes unique to co-exposure (DE+allergen), undetected with mono-exposures (DE or allergen alone). Validation studies confirmed that specific proteins ( e.g. the antimicrobial peptide cystatin-SA) were significantly enhanced with DE+allergen compared to either mono-exposure. This study demonstrates that common environmental co-exposures can uniquely alter protein responses in the lungs, illuminating biology that mono-exposures cannot. This study highlights the value of complex human in vivo models in detailing airway responses to inhaled pollution. Allergen-induced proteins secreted in airways are altered by diesel exhaust, in a controlled exposure human model http://ow.ly/gaqh30h4Isi